2017
DOI: 10.1093/femsec/fix059
|View full text |Cite
|
Sign up to set email alerts
|

Non-Redfield, nutrient synergy and flexible internal elemental stoichiometry in a marine bacterium

Abstract: The stoichiometric constraints of algal growth are well understood, whereas there is less knowledge for heterotrophic bacterioplankton. Growth of the marine bacterium Phaeobacter inhibens DSM 17395, belonging to the globally distributed Roseobacter group, was studied across a wide concentration range of NH4+ and PO43−. The unique dataset covers 415 different concentration pairs, corresponding to 207 different molar N:P ratios (from 10−2 to 105). Maximal growth (by growth rate and biomass yield) was observed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…The capacity to rapidly store nitrogen internally possibly reflects the strong influence of NH 4 + availability on the growth of P. inhibens DSM 17395 (Trautwein et al. 2017 ) and in more general terms an adaptation to fluctuating NH 4 + supply. The latter is expected to occur frequently in the natural habitat of the studied roseobacters: on a larger scale in coastal regions and on a microcosm-scale on marine snow particles representing nutrient-rich hotspots in otherwise oligotrophic water columns (Azam and Long 2001 ; Gram et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The capacity to rapidly store nitrogen internally possibly reflects the strong influence of NH 4 + availability on the growth of P. inhibens DSM 17395 (Trautwein et al. 2017 ) and in more general terms an adaptation to fluctuating NH 4 + supply. The latter is expected to occur frequently in the natural habitat of the studied roseobacters: on a larger scale in coastal regions and on a microcosm-scale on marine snow particles representing nutrient-rich hotspots in otherwise oligotrophic water columns (Azam and Long 2001 ; Gram et al.…”
Section: Resultsmentioning
confidence: 99%
“…2017). Considering the important role of NH 4 + for growth of P. inhibens DSM 17395 in particular and the general relevance of this macronutrient for the productivity of marine heterotrophic bacteria, the present study aims at investigating the NH 4 + acquisition and processing strategies of P. inhibens DSM 17395 as a well-studied representative of the Roseobacter group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two Rhodobacterales genera responded to oil amendment, which is consistent with previous reports (Chakraborty et al, 2012). Rhodobacterales ( Phaeobacter ) are commonly reported to be marine heterotrophs capable of growing on a wide range of nitrogen and phosphorous concentrations and in a wide range of temperatures (Lee et al, 2016; Trautwein et al, 2017; Wienhausen et al, 2017). Unclassified Kiloniellales ( Kiloniellaceae ) also responded to oil amendment, and, although many are host associated (Soffer et al, 2015; Cleary et al, 2016; Lawler et al, 2016), one member of this order was isolated and reported as a chemoheterotrophic aerobe that may be involved in denitrification (Wiese et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nutrient loading is often linked with the limitation of diatom growth due to silicate deficiency and the proliferation of non-siliceous, unpalatable algae (Officer and Ryther 1980, Breton et al 2006, Panizzo et al 2018. Alternatively, primary producers and heterotrophic bacteria may utilize inorganic nutrients outside the Redfield ratio thus altering their intracellular C:N:P ratio (Mills and Arrigo 2010, Meunier et al 2014, Trautwein et al 2017).…”
Section: Introductionmentioning
confidence: 99%